Are women nursing academics represented in university leadership positions? - Livesay, Karen; Walter, Ruby; Petersen, Sacha; Zhao, Lin (Journal of University Teaching and Learning Practice, 2022)
The nursing workforce constitutes the largest professional health workforce in Australia. Nursing is traditionally a female dominated profession. This study reviewed Australian universities that provide entry to practice nursing education. The study identified the distribution of females and males in leadership in nursing education, the positioning of the discipline in the university, and where nurses occupy leadership roles above the nursing discipline (faculty/college). Of the 37 universities that offered entry to practice nursing, more females were evident. However, more men were evident in academia than the proportion of men in nursing outside of the academic setting. Leadership nomenclature varied within each nursing discipline group reviewed. This study demonstrated that the number of nursing academics has decreased since the late 1990’s. The nursing workforce is still a significant contributor to the academic workforce and yet numbers of nurse academics working in roles senior to their discipline were few. This paper discusses how the nursing workforce as predominantly female, has implications to both females and males, and may impact opportunities for leadership and promotion to senior roles.